Hormonal Study of Primary Infertile Women - Rashid, Ban Mousa; Nore, Beston F.; Mahmoud, Tayfoor Jalil (Sulaimani Journal for Pure and Applied Sciences, 2013)
Approximately (15 %) of couples attempting their first pregnancy meet with failure. Most authorities define these patients as being primary infertile if they unable to achieve a pregnancy after one year of unprotected intercourse. The aim of this study was to evaluate the serum levels of Luteinizing hormone, Follicle stimulating hormone, Prolactin and Testosterone in (410) primary infertile women in Sulaimani city. The results obtained compared with that of (240) age matched fertile women. The results showed, higher incidence of primary infertility was in the age range (26-37) years and hormonal imbalance plays an important role in primary female infertility.
Keywords: Primary female infertility; LH; FSH; PRL; Testosterone